AZI2 positively regulates the induction of type I interferon in influenza-trigger pediatric pneumonia. Issue 1 (20th May 2022) - Wei, Meili; Zheng, Yanfei; Xu, Jing; Sun, Qiwei
Abstract: 5-azacytidine-induced protein 2 (AZI2) is known to have a crucial role in antiviral innate immunity. This study aims to explore the roles of AZI2 in influenza-trigger pediatric pneumonia and its molecular mechanism. qPCR and immunoblotting assays were used to determine the levels of target genes and proteins. The lung infection mouse model was established by using PR8 H1N1 virus in AZI2 germline knockout (AZI2 −/− ) and wild-type (WT) mice. In addition, HEK293T cell-based luciferase reporter assays were used to investigate the regulatory effects of AZI2 on type I interferon. Immune precipitation and immunofluorescence staining were used to evaluate the interactions between AZI2 and TANK binding kinase 1 (TBK1). We observed an elevation in the expressions of IFN-I and AZI2 in peripheral blood mononuclear cells from the pneumonia patients with mild symptoms. Interestingly, AZI2 deficiency deteriorated the influenza-induced pathological symptoms in the lung as well as reduced the survival rate. It was further showed that AZI2 positively regulated the expressions of type I interferon, inflammatory cytokines, and IFN production-related genes. The molecular mechanism data revealed that AZI2 regulated the interactions between TBK1 and TANK. In summary, AZI2 positively regulates type I interferon production in influenza-induced pediatric pneumonia by promoting the interactions between TBK1 and TANK. Abstract : AZI2 positively regulates type I interferon production in influenza-induced pediatric pneumonia by promoting the interactions between TBK1 and TANK.